Transactions of the American Mathematical Society. Volume 349, Number 5, 1997 - American Mathematical Society (American Mathematical Society, 2009)
Contents of Volume 349, Number 5 View front matter and back matter from the print issue of this journal View front and back matter from the print issue All articles in this issue are available free of charge